Baicalin protects retinal ganglion cells by regulating microglial polarization and ferroptosis via the JAK2/STAT3 pathway - Yu, Huan; Xu, Tianzhao; Feng, Qiaozong; Wang, Yilin; Zou, Jun; Ma, Xiaoyun (Frontiers in Pharmacology, 2025)
IntroductionThis study investigated the protective effects of baicalin on retinal ganglion cells (RGCs) subjected to ischemia-reperfusion injury and explored the underlying mechanisms.MethodsBy establishing an in vitro model of oxygen-glucose deprivation/reperfusion (OGD/R) in a microglia-RGC co-culture system, we examined the protective role of baicalin against RGC injury.ResultsThe results demonstrated that baicalin significantly suppressed the M1 polarization of microglia, promoted their shift toward M2 polarization, and alleviated oxidative stress and ferroptosis in RGCs by inhibiting the JAK2/STAT3 signaling pathway.ConclusionThis study reveals that baicalin protects RGCs by modulating microglial polarization and inhibiting ferroptosis, providing novel insights for the treatment of glaucoma.